ANALISIS YURIDIS PERATURAN PEMERINTAH REPUBLIK INDONESIA NOMOR 21 TAHUN 2020 - Marita Lely Rahmawati (Fakultas Hukum Universitas Islam Malang, 2021)
ABSTRACT The emergence of Corona Virus Disease 2019 or COVID-19 which can be transmitted quickly from one person to another at close range and in severe cases can result in death, causing several countries to take preventive steps to control the spread of this virus. Several steps were taken to close access to social mobilization of the community and physical human interactions by quarantining areas or known as “Lockdown” in several European, American and Asian countries. In the Indonesian Laws and Regulations, the term Regional Quarantine and Large-Scale Social Restrictions are known, which essentially have the same goal as Lockdown. The President then issued Government Regulation of the Republic of Indonesia Number 21 of 2020 as an implementing regulation of Law of the Republic of Indonesia Number 6 of 2018 which is used as the legal basis for implementing Large-Scale Social Restrictions. However, the formation of this Government Regulation does not fulfill several provisions in the formation of Laws and Regulations stipulated in Law of the Republic of Indonesia Number 12 of 2011 Jo. Law of the Republic of Indonesia Number 15 of 2019. As the result, this Government Regulation can not function properly.Keywords : Government Regulation of the Republic of Indonesia Number 21 of 2020, Law of the Republic of Indonesia Number 12 of 2011, Law of the Republic of Indonesia Number 15 of 2019. ABSTRAK Kemunculan Corona Virus Disease 2019 atau COVID-19 yang dapat menular dengan cepat dari satu orang ke orang lain dalam jarak dekat dan pada kasus yang berat dapat mengakibatkan kematian, menyebabkan beberapa negara melakukan langkah-langkah preventif dalam mengendalikan laju penyebaran virus ini. Beberapa langkah diambil untuk menutup akses mobilisasi sosial masyarakat serta interaksi fisik manusia dengan mengkarantina wilayah atau dikenal dengan istilah “Lockdown” di beberapa negara-negara Eropa, Amerika dan Asia. Dalam Peraturan Perundang-undangan Indonesia dikenal istilah Karantina Wilayah dan istilah Pembatasan Sosial Berskala Besar yang pada intinya memiliki tujuan yang sama dengan Lockdown. Presiden kemudian menerbitkan Peraturan Pemerintah Republik Indonesia Nomor 21 Tahun 2020 sebagai peraturan pelaksana Undang-Undang Republik Indonesia Nomor 6 Tahun 2018 yang digunakan sebagai dasar hukum penerapan Pembatasan Sosial Berskala Besar. Namun, pembentukan Peraturan Pemerintah ini tidak memenuhi beberapa ketentuan pembentukan Peraturan Perundang-undangan yang diatur di dalam Undang-Undang Republik Indonesia Nomor 12 Tahun 2011 Jo. Undang-Undang Republik Indonesia Nomor 15 Tahun 2019. Akibatnya, Peraturan Pemerintah ini tidak dapat berfungsi dengan baik.Kata Kunci: Peraturan Pemerintah Republik Indonesia Nomor 21 Tahun 2020, Undang-Undang Republik Indonesia Nomor 12 Tahun 2011, Undang-Undang Republik Indonesia Nomor 15 Tahun 2019.